2012
DOI: 10.1111/j.1365-2672.2012.05425.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic strain heterogeneity within a natural population ofOenococcus oenifrom Amarone wine

Abstract: Remarkable intraspecies complexity within the O. oeni natural population could explain the great versatility of this species as key of successful adaptation to harsh winemaking conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Moreover, our preliminary discrimination by PFGE associated with a further analysis of strain discrimination level by DD-PCR revealed a better estimation of strain heterogeneity of O. oeni populations as previously demonstrated by Lechiancole et al (2006) confirming that this species is characterized by high intra-species diversity (Sato et al 2001;Cappello et al 2008Cappello et al , 2010Vigentini et al 2009;Solieri et al 2010;Zapparoli et al 2012). These results are supported by the peculiarity of Aglianico del Vulture wine vinification where low temperatures, pH generally below 3.5, and high ethanol content are selective features for the indigenous microflora; and at the same time, it is possible that the typical characteristics of the products are due, at least partially, to the high degree of heterogeneity, confirmed by the clusters obtained.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Moreover, our preliminary discrimination by PFGE associated with a further analysis of strain discrimination level by DD-PCR revealed a better estimation of strain heterogeneity of O. oeni populations as previously demonstrated by Lechiancole et al (2006) confirming that this species is characterized by high intra-species diversity (Sato et al 2001;Cappello et al 2008Cappello et al , 2010Vigentini et al 2009;Solieri et al 2010;Zapparoli et al 2012). These results are supported by the peculiarity of Aglianico del Vulture wine vinification where low temperatures, pH generally below 3.5, and high ethanol content are selective features for the indigenous microflora; and at the same time, it is possible that the typical characteristics of the products are due, at least partially, to the high degree of heterogeneity, confirmed by the clusters obtained.…”
Section: Discussionsupporting
confidence: 72%
“…As regards the usefulness of the methods assayed in this study, there were important discrepancies among authors. So far, most authors agree that PFGE typing by using appropriate restriction endonucleases gives the greatest discriminatory power and the highest reproducibility (Lopez et al 2007(Lopez et al , 2008GonzalezArenzana et al 2011;Zapparoli et al 2012;Pramateftaki et al 2012); on the contrary, Ruiz et al (2008) reported PFGE analysis using restriction enzyme ApaI or SfiI showed poorer discriminant capacity than RAPD-PCR, and also evaluated DD-PCR method not suitable for their typing purposes. This is in disagreement with Lechiancole et al (2006) that evidenced the reliability of the DD-PCR in the differentiation of closely related strains suggesting that this method can represent an alternative and/or additional tool for fine characterization of oenococcal strains.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The bacterial genomes have been shown to be highly plastic and are frequently reorganized through genetic rearrangements and gene transfer, which can help them adapt to distinct ecological conditions [38]. High level of heterogeneity and diversity among strains were observed under stressful ecosystem such as high ethanol content, low pH and temperature [39]. Alcohol ingested orally is transported to the colon by blood circulation, and due to its high water solubility, intracolonic ethanol levels are equal to those in the blood [40].…”
Section: Discussionmentioning
confidence: 99%
“…During MLF, O. oeni strains can influence the aroma and flavour of wines by the production of volatile metabolites and the modification of aroma precursors derived from grapes and yeasts. It has been increasingly recognised that O. oeni exhibits a broad range of secondary metabolic activities during MLF, especially hydrolysis of glycosides, which plays a primary role in the expression of flavour characteristics of grape and wine (Mesas et al 2012;Michlmayr et al 2012a;Zapparoli et al 2012;Dong et al 2014).…”
mentioning
confidence: 99%